2020
DOI: 10.1111/ijpo.12614
|View full text |Cite
|
Sign up to set email alerts
|

Executive functioning and disinhibited eating in children and adolescents

Abstract: Background: Executive functioning (EF) difficulties may be associated with problems regulating eating behaviours. Few studies have evaluated this question in youth using diverse measures of EF or objective measures of energy intake. Methods:The current study used neuropsychological tasks and a laboratory test meal to evaluate the links between EF and youth's disinhibited eating patterns.Two-hundred-five nontreatment seeking youth (M age = 13.1 ± 2.8 years; M BMIz = 0.6 ± 1.0; 33.2% overweight; 54.1% female) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 76 publications
3
16
0
1
Order By: Relevance
“…Similarly, overall diet quality is poorer in patients with ADHD [ 7 ], mania [ 8 ], and addictions [ 9 ] compared to unaffected individuals. Disinhibited eating, or the tendency to overeat in response to different stimuli including external food cues and stress, is associated with higher energy intake, higher BMI, and elevated obesity risk [ 10 , 11 ], as well as with more general indicators of behavioral disinhibition such as ADHD symptoms [ 12 , 13 ] and poor executive functioning task performance [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, overall diet quality is poorer in patients with ADHD [ 7 ], mania [ 8 ], and addictions [ 9 ] compared to unaffected individuals. Disinhibited eating, or the tendency to overeat in response to different stimuli including external food cues and stress, is associated with higher energy intake, higher BMI, and elevated obesity risk [ 10 , 11 ], as well as with more general indicators of behavioral disinhibition such as ADHD symptoms [ 12 , 13 ] and poor executive functioning task performance [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…While this study investigated and did not find an association between experimental tasks assessing EF and EAH, the authors acknowledged that their sample ( N = 29) may have been too small to find such effects (Pieper and Laugero, 2013 ). Indeed, a broader literature on EF abilities has shown that it is meaningfully related to eating behaviors in preschool- (Allom and Mullan, 2014 ; Levitan et al, 2015 ; Reimann et al, 2020 ) and school-aged (Riggs et al, 2010a , b ; Nederkoorn et al, 2015 ; Kelly et al, 2020 ) children (but see Hughes et al, 2015 ; Tan and Lumeng, 2018 ). A few studies have compared subdomains of EF (e.g., inhibitory control, updating), and suggest that they may be uniquely related to eating behavior (Allom and Mullan, 2014 ; Gettens and Gorin, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, inhibitory control deficits (i.e., reduced ability to suppress or interrupt prepotent responses) can interfere with self-regulation processes, including the ability to modulate the types and amount of food consumed ( Liang et al, 2014 ) and are a specific facet of executive functioning that may be related to LOC eating. In fact, a recent study found that inhibitory control deficits, assessed with the stop-signal task, were the only executive functioning measure associated with caloric consumption during a laboratory test meal – an objective measure of LOC eating ( Kelly et al, 2020 ).…”
Section: Executive Functioning As a Mechanism Linking Activity And Lomentioning
confidence: 99%